2016
DOI: 10.1002/icd.1958
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Fathers' Physical and Toy Play and Links to Child Behaviour: An Exploratory Study

Abstract: Increasing amounts of research show that fathers' involvement in children's lives contributes to the child's social, emotional and cognitive development; however, much of the evidence comes from fathers' caregiving and object play. This exploratory study compared the characteristics of 24 Australian fathers' play in two contexts -toy play and physical play -and examined the association of these play contexts with children's development. Correlational analyses revealed few conceptual similarities between toy pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 65 publications
0
30
0
1
Order By: Relevance
“…For a sample size of 42, the inclusion of four predictors was expected to provide a good estimate of coefficients (Austin & Steyerberg, ; Knofczynski & Mundfrom, ). Child temperament variables were entered before parenting attitudes because child temperament may exert a stronger effect on fathers’ parenting than on mothers (McBride, Schoppe, & Rane, ), and previous studies have found that father report of parenting warmth, consistency, and reasoning style was unrelated to father–child RTPQ quality (StGeorge et al., ). Results for the regression model are reported in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a sample size of 42, the inclusion of four predictors was expected to provide a good estimate of coefficients (Austin & Steyerberg, ; Knofczynski & Mundfrom, ). Child temperament variables were entered before parenting attitudes because child temperament may exert a stronger effect on fathers’ parenting than on mothers (McBride, Schoppe, & Rane, ), and previous studies have found that father report of parenting warmth, consistency, and reasoning style was unrelated to father–child RTPQ quality (StGeorge et al., ). Results for the regression model are reported in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The father–child overall RTPQ score was associated with fewer child emotional and behavioral problems, as rated by both mothers and fathers (Fletcher et al., ). In a second study, father–child overall RTPQ score predicted fewer mother‐rated child emotional and behavior difficulties (StGeorge, Fletcher, & Palazzi, ). These authors have suggested that the intimate context of father–child RTP may provide children with opportunities to practice complex prosocial skills, regulate aggressive impulses, and sustain reciprocal play.…”
Section: Child Aggression Social Dominance and Father–child Rtpmentioning
confidence: 98%
“…During early life, play is a ubiquitous activity, and engaging in play is positively associated with the development of social skills, cognitive skills, language and emotional well-being (Fung & Cheng, 2017; Lyytinen, Laakso, Poikkeus & Rita, 1999; Pellegrini, Kato, Blatchford & Baines, 2002; St George, Fletcher & Palazzi, 2016; Thibodeau, Gilpin, Brown, & Meyer, 2016). Current conceptualisations of play in the behavioural sciences view it in broad terms as behaviour that is voluntary, engaging, non-functional, and associated with the expression of positive affect (Burghardt, 2005; Lillard et al, 2013; Miller 2017).…”
Section: Introductionmentioning
confidence: 99%
“…what is the individual playing with? For example, physical play is play with one’s own body and other people, for example, climbing, sliding, chasing (Pellegrini et al, 2002; Power, 1999; St George et al, 2016;); sociodramatic or pretend play is play with a make-believe world, and the focus of play is more than a concrete observable entity (Lillard et al, 2013); games with rules involve playing with a set of rules that participants agree to abide by to partake in the play experience, for example, board games or playground games such as tag (Hassinger-Das et al, 2017); and functional/exploratory play involves playing with physical objects, such as toys and blocks, and includes constructing models or making things (Pellegrini & Gustafson, 2005; Power, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation